Development of Community Social Workers - Julita Mina Harafah, Putri; Jamaris, Jamaris; Irmawita, Irmawita (Universitas Negeri Padang, 2024)
The basic idea of linking various social welfare development services is to distribute charity equally across the nation in accordance with human rights standards. Based on human rights, quality services have become a necessity. Social services are very important because human rights requirements and good quality services are needs that cannot be denied. Therefore, social services need to be planned systematically and meet the standardization of service quality in line with the philosophy and professional needs of the state. In the future, in the conditions and situations of the development of social problems and community demands, social workers are needed to lead social welfare development programs and policies, based on justice for all and protection of human rights. So, the writing of this article aims to change the way people think and promote the existence of social workers as a profession in the eyes of the public, not only as a non-profit activity, but as a profession with knowledge, skills and values in practice.